Properties of stabilized peat by soil-cement column method - Hashim, Roslan; Islam, M.S. (2008)
A field model study has been carried out to stabilise peat soil using various types of binder by deep mixing method and to investigate its effect on engineering properties. Some soil-cement model columns have been constructed at site and different mechanical properties of stabilised peat, like undrained shear strength, unconfined compressive strength and shear strength was determined after 14 days of curing time. Scanning Electron Micrograph (SEM) and Energy Dispersive X-Ray (EDX) test were also conducted to observe the microstructure of stabilised peat soil. From the test result it was observed that the engineering properties of peat soil can be improved by stabilisation using additives.